2008
DOI: 10.1158/1078-0432.ccr-07-5050
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Rarefaction during Treatment with Telatinib, a Small Molecule Angiogenesis Inhibitor

Abstract: Purpose: Hypertension is a commonly reported side effect in antiangiogenic therapy.We investigated the hypothesis that telatinib, a small molecule angiogenesis inhibitor, impairs vascular function, induces rarefaction, and causes hypertension. Experimental Design: A side-study was done in a phase I trial of telatinib, a small molecule tyrosine kinase inhibitor of vascular endothelial growth factor receptors 2 and 3, platelet-derived growth factor receptor, and c-KIT in patients with advanced solid tumors. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(109 citation statements)
references
References 41 publications
4
100
2
3
Order By: Relevance
“…5 Indeed, prolonged treatment with the RTKIs sunitinib and telatinib has been reported to be associated with capillary rarefaction. 9,25,26 To increase vascular resistance in a particular vascular bed by 5%, it has been estimated that 40% rarefaction of fourth-order vessels is required. 27 It is inconceivable that such an extensive degree of systemic rarefaction can occur within 4 hours after initiation of angiogenesis inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Indeed, prolonged treatment with the RTKIs sunitinib and telatinib has been reported to be associated with capillary rarefaction. 9,25,26 To increase vascular resistance in a particular vascular bed by 5%, it has been estimated that 40% rarefaction of fourth-order vessels is required. 27 It is inconceivable that such an extensive degree of systemic rarefaction can occur within 4 hours after initiation of angiogenesis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, clinical studies, using flow-mediated dilatation (FMD) as an index of NO bioavailability, do not unequivocally support the hypothesis that a decrease in NO bioavailability underlies the increase in MABP, because decreases in both endothelium-dependent and endothelium-independent vasodilatation have been reported in patients treated with RTKIs. 8,9 In previous clinical and experimental studies, we and others have shown that activation of the endothelin (ET) system is involved in the sunitinib-induced rise in MABP. 10 -12 Apart from inducing vasoconstriction, ET-1 activates vascular NADPH oxidase, leading to an increase in oxidative stress through enhanced reactive oxygen species (ROS) production.…”
mentioning
confidence: 99%
“…However, the off-target and broad-spectrum activity associated with these multitargeted drugs confers them with a unique toxicity profile (61)(62)(63). At present, 6 targeted agents are approved for the treatment of metastatic RCC in Europe and/or the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension as a common class toxicity phenomenon was clinically well manageable in most of the patients with a standard antihypertensive treatment. Recently, Steeghs et al (2008) reported that small vessel rarefaction may be one of the underlying haemodynamic mechanisms causing hypertension. The average increase in diastolic blood pressure in our study was comparable to those reported results.…”
Section: Discussionmentioning
confidence: 99%